Hydroxycarboxylic Acid Receptor 2, a Pleiotropically Linked Receptor for the Multiple Sclerosis Drug, Monomethyl Fumarate. Possible Implications for the Inflammatory Response - Parodi, Benedetta; Sanna, Alessia; Cedola, Alessia; Uccelli, Antonio; Kerlero de Rosbo, Nicole (Frontiers in Immunology, 2021)
Monomethyl fumarate (MMF), metabolite of dimethyl fumarate (DMF), an immunosuppressive drug approved for the treatment of multiple sclerosis (MS), is a potent agonist for hydroxycarboxylic acid receptor 2 (HCAR2), eliciting signals that dampen cell activation or lead to inflammation such as the skin flushing reaction that is one of the main side effects of the treatment, together with gastrointestinal inflammation. Our aim is to further understand the molecular basis underlying these differential effects of the drug. We have used wild-type and HCAR2 knock-out mice to investigate, in vitro and ex vivo under steady-state and pathological conditions, the HCAR2-mediated signaling pathways activated by MMF in dendritic cells (DC), which promote differentiation of T cells, and in intestinal epithelial cells (IEC) where activation of a pro-inflammatory pathway, such as the cyclooxygenase-2 pathway involved in skin flushing, could underlie gastrointestinal side effects of the drug. To understand how DMF treatment might impact on gut inflammation induced by experimental autoimmune encephalomyelitis (EAE), the animal model for MS, we have used 3D X-ray phase contrast tomography and flow cytometry to monitor possible intestinal alterations at morphological and immunological levels, respectively. We show that HCAR2 is a pleiotropically linked receptor for MMF, mediating activation of different pathways leading to different outcomes in different cell types, depending on experimental in-vitro and in-vivo conditions. In the small intestine of EAE-affected mice, DMF treatment affected migration of tolerogenic DC from lamina propria to mesenteric lymph nodes, and/or reverted their profile to pro-inflammatory, probably as a result of reduced expression of aldehyde dehydrogenase and transforming growth factor beta as well as the inflammatory environment. Nevertheless, DMF treatment did not amplify the morphological alterations induced by EAE. On the basis of our further understanding of MMF signaling through HCAR2, we suggest that the pleiotropic signaling of fumarate via HCAR2 should be addressed for its pharmaceutical relevance in devising new lead compounds with reduced inflammatory side effects.